Etika Guru BK Disabilitas Netra dalam Praktik Mengajar Bimbingan Konseling - Saputri, Toviyani Widi; Rukiyati, Rukiyati (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
Ethics are the foundation used by all professions in carrying out their duties. No exception for guidance and counseling teachers, they also apply ethics in carrying out professional duties. There have been many studies discussing teacher ethics, but none have discussed ethics regarding blind guidance and counseling teachers.The method used in this study is qualitative with a case study approach on guidance and counseling teachers who are still actively teaching at private MTS in the city of Yogyakarta. Data collection was carried out by means of in-depth interviews and non-participatory observation The results of the study showed that in conditions of visual disabilities, guidance and counseling teachers still carry out ethics as they should. There is even a certain way to apply these ethics to students who also have a number of the same disabilities.